PAMERAN SEJARAH DAN KEBUDAYAAN SEBAGAI SARANA LITERASI GLOBAL PELAJAR ABAD-21 - Cut Putroe Yuliana; Nurhayati Ali Hasan; Viona Febiyola Bakkara
History and culture exhibitions are activities that display various artifacts, documents, artworks, and informative materials related to historical and cultural heritage, with the aim of introducing, preserving, and educating the public about historical values, traditions, arts, and cultural practices. This study aims to explore the capabilities of Meusuraya Akbar's history and culture exhibition in enhancing global literacy for 21st century learners. The research conceptual framework refers to Clifford Geertz's theory and the Museum Learning Model that emphasizes culture as a system of symbols and meanings that are contextual, participatory and multisensory. The research approach used is quantitative with simple linear regression analysis. The research was conducted at the Balee Meusapat Ureung Pidie Building during the exhibition. The research sample consisted of 96 high school students who visited the exhibition, selected using the Lemeshow formula with purposive sampling technique. Data collection was done through questionnaires and documentation. Data analysis using linear regression resulted in the equation Y = 7.659 + 0.267 X. The constant value of 7.659 indicates the basic level of global literacy of 21st century students. The coefficient of history and culture exhibition (X) of 0.267 indicates that every one unit increase in the influence of the exhibition will increase global literacy by 0.267 units. The significance test yielded a p-value of 0.000 (<0.05), which confirms the acceptance of the alternative hypothesis (Ha) and indicates the exhibition's capability as a significant global literacy medium. The coefficient of determination (R²) of 0.259 states that 25.9% of the variance in global literacy (Y) can be explained by history and culture exhibitions (X). This finding proves that the Meusuraya Akbar History and Culture Exhibition has a measurable impact on improving the global literacy of 21st century learners, so it can act as an effective educational medium.